Peripheral immunity involvement in the cognitive impairment of sporadic amyotrophic lateral sclerosis - Yang, Tianmi; Wei, Qianqian; Li, Chunyu; Ou, Ruwei; Lin, Junyu; Cheng, Yangfan; Xiao, Yi; Shang, Huifang (Frontiers in Neurology, 2024)
Background Recent research has indicated the significance of immune activation in amyotrophic lateral sclerosis (ALS). However, the impact of peripheral immunity on cognitive impairment in sporadic ALS remains poorly characterized. Therefore, we aim to assess the relationship between peripheral immune parameters and cognitive impairment in patients with sporadic ALS. Methods A case–control study involving 289 patients with sporadic ALS was conducted. All participants underwent cognitive assessment and measurements of blood immune parameters. The main outcomes included adjusted odds ratios (ORs) in multivariate logistic regression analysis and adjusted coefficients in a multivariate linear regression model. Sensitivity analysis was performed with stratification by the King’s clinical stage. Results Cognitive impairment was observed in 98 (33.9%) patients. Higher counts of leukocyte (OR, 0.53; 95% CI, 0.29 to 0.95; p = 0.03), neutrophil (OR, 0.48; 95% CI, 0.26 to 0.88; p = 0.02), and monocyte (OR, 0.33; 95% CI, 0.18 to 0.60; p < 0.001) were significantly associated with better cognitive preformence in sporadic ALS, particularly among patients in King’s clinical stages 1 and 2. Conversely, a higher percentage of CD4+ T cells was linked to an increased risk of cognitive impairment (OR, 2.79; 95% CI, 1.52 to 5.09; p = 0.001), particularly evident in patients in King’s clinical stage 3. Conclusion These results highlight the involvement of peripheral immunity in the cognitive impairment of sporadic ALS and suggest dynamic and intricate roles that vary across disease stages. Elucidating the links between immunity and ALS sheds light on the pathophysiological mechanisms underlying this fatal neurodegenerative disorder and informs potential immunotherapeutic strategies.